La costruzione del visibile: sperimentazioni luminose tra arte e scienza - Porcheddu, Federica (Scenari, 2025)
This paper explores the turning point made by twentieth-century experimental photography through the research of Man Ray (Electricité photograms and series) and László Moholy-Nagy (Light-Space Modulator), in which light is conceived as an active principle in image formation. He then delves deeper into the thought of György Kepes at the New Bauhaus Institute in Chicago, where in the volumes Language of Vision (1944) and The New Landscape in Art and Science (1956) he combines Gestalt psychology, scientific methods and creativity, proposing light as a generating principle of form and meaning. Analyzing photograms, kinetic installations, and macroradiographs, the article demonstrates how light shapes perception and symbols, proposing a multidisciplinary method for navigating the algorithmic “invisible” of the contemporary digital landscape.